Analysis of rhizosphere soil microbial diversity and its functions between Dahongpao mother tree and cutting Dahongpao - Jia, Xiaoli; Li, Mingzhe; Zhang, Qi; Jia, Miao; Hong, Lei; Zhang, Shuqi; Wang, Yuhua; Luo, Yangxin; Wang, Tingting; Ye, Jianghua; Wang, Haibin (Frontiers in Plant Science, 2024)
Dahongpao mother tree (Camellia sinensis (L.) O. Ktze) is a representative of Wuyi rock tea. Whether there is a difference in rhizosphere soil microbial diversity and function between asexually propagated cuttings of Dahongpao (PD) and the parent Dahongpao mother tree (MD) has not been reported. In this study, high throughput sequencing technology was used to analyze the rhizosphere soil microbial diversity, functions and their relationship with soil available nutrients and enzyme activities in MD and PD. The results showed that available nitrogen, phosphorus and potassium contents and urease, protease, acid phosphatase and sucrase activities of rhizosphere soils in MD were significantly higher than those in PD. Both bacterial and fungal diversity were higher in rhizosphere soils in MD than in PD, and secondly, the bacterial community structure was less stable while the fungal community structure was more stable in PD compared to MD. There were significant differences between MD and PD tea tree rhizosphere soils in 6 genera of characteristic bacteria and 4 genera of characteristic fungi. The results of function and interaction effect analysis showed that the rhizosphere soil available nutrient content and enzyme activities in MD were significantly higher than those in PD, and their contributions mainly originated from Pirellula and Acidisphaera of characteristic bacteria and Alatospora of characteristic fungi. Secondly, MD maybe had a stronger ability to inhibit soil pathogens than PD, with the main contribution coming from Scopulariopsis and Tolypocladium of characteristic fungi. Overall, compared with PD, the soil texture in MD was relatively better, and its soil nutrient cycling-related enzyme activities were stronger, which was more favorable to soil nutrient cycling and increased the available nutrient content of the soil, which in turn promoted the growth of tea trees. This study provides an important reference for the planting and management of tea tree cuttings and microbial regulation of tea tree growth.